Gonadal sexual differentiation of European sea bass (Dicentrarchus labrax, L. 1758) of fingerlings in different size classes. Issue 5 (2nd September 2016) - Guerrera, Maria Cristina; Arfuso, Francesca; Rizzo, Maria; Saoca, Concetta; Fazio, Francesco; Fortino, Gianluca; Santulli, Andrea; Piccione, Giuseppe
Abstract: This report describes a study of the gonad differentiation in fingerlings of European sea bass ( Dicentrarchus labrax ) belonging to different size groups. Fishes were divided into four groups according to their weight: Group 1 (4.5 ± 0.7 g), Group 2 (9.2 ± 0.8 g), Group 3 (14.8 ± 1.8 g), and Group 4 (21.8 ± 2.3 g). In all groups, low percentages of undifferentiated or early sexually differentiated fish were found. Higher percentages of fully differentiated ovaries were found in Groups 1 and 3. Fully differentiated testes occurred in 90% of Group 4. Ninety percent of fish in Group 2 had gonads with intratesticular oocytes. This highlights the occurrence of intersexual cases and suggests that at this size, the fish is susceptible to phenotypic plasticity. The results of the present study show that sexual differentiation of the gonads is found in fish at 4.5 g weight. The ambiguous relationship between the observed gonad morpho-functional characteristics and fish size suggests a subject-dependent sexual differentiation.